2008
DOI: 10.1371/journal.pone.0001959
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Relational Memory Requires Hippocampal Adult Neurogenesis

Abstract: The dentate gyrus of the hippocampus is one of the few regions of the mammalian brain where new neurons are generated throughout adulthood. This adult neurogenesis has been proposed as a novel mechanism that mediates spatial memory. However, data showing a causal relationship between neurogenesis and spatial memory are controversial. Here, we developed an inducible transgenic strategy allowing specific ablation of adult-born hippocampal neurons. This resulted in an impairment of spatial relational memory, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
453
3
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 527 publications
(497 citation statements)
references
References 78 publications
27
453
3
5
Order By: Relevance
“…When testing spatial memory ability, deficits were described in some studies (Snyder et al 2005;Fan et al 2007;Dupret et al 2008;FarioliVecchioli et al 2008;Imayoshi et al 2008;Garthe et al 2009;Lemaire et al 2012), but not in others (Shors et al 2002;Madsen et al 2003;Raber et al 2004;Meshi et al 2006;Saxe et al 2006;Winocur et al 2006;Wojtowicz et al 2008). From our own study, based on a model that consisted in selectively ablating adult hippocampal neurogenesis by overexpressing the proapoptotic protein Bax in neuronal precursors on administration of doxycycline, we concluded that adult-born neurons are required for an allocentric (and not egocentric) strategy and for the flexible use of the acquired information (Dupret et al 2008).…”
Section: Causationmentioning
confidence: 62%
See 1 more Smart Citation
“…When testing spatial memory ability, deficits were described in some studies (Snyder et al 2005;Fan et al 2007;Dupret et al 2008;FarioliVecchioli et al 2008;Imayoshi et al 2008;Garthe et al 2009;Lemaire et al 2012), but not in others (Shors et al 2002;Madsen et al 2003;Raber et al 2004;Meshi et al 2006;Saxe et al 2006;Winocur et al 2006;Wojtowicz et al 2008). From our own study, based on a model that consisted in selectively ablating adult hippocampal neurogenesis by overexpressing the proapoptotic protein Bax in neuronal precursors on administration of doxycycline, we concluded that adult-born neurons are required for an allocentric (and not egocentric) strategy and for the flexible use of the acquired information (Dupret et al 2008).…”
Section: Causationmentioning
confidence: 62%
“…To summarize, a clear disruption of trace eye-blink conditioning has been described (Shors et al 2001(Shors et al , 2002, whereas conflicting results have been reported for contextual fear conditioning. Although some studies reported impairment in generating and/or retrieving contextual fear memory Winocur et al 2006;Farioli-Vecchioli et al 2008;Imayoshi et al 2008;Wojtowicz et al 2008;Deng et al 2009;Hernandez-Rabaza et al 2009), opposite results were found in other studies (Shors et al 2002;Clark et al 2008;Dupret et al 2008;Kitamura et al 2009). …”
Section: Causationmentioning
confidence: 86%
“…In the healthy adult brain, neurogenesis is necessary to maintain neurological function. Ablation of NPCs from the dentate gyrus reduces neurogenesis and impairs functional plasticity, showing the importance and necessity of neurogenesis after brain injury (57,58).…”
Section: Growth-promoting Environmentmentioning
confidence: 99%
“…With this single goal, equimolecular doses to 50 mg/kg BrdU for both CldU (5-chloro-2 0 -deoxyuridine) and IdU (5-iodo-2 0 -deoxy-uridine) were calculated as published elsewhere (Llorens-Martin et al, 2010), and accordingly to the findings recently published (Dupret et al, 2008;Leuner et al, 2009).…”
Section: Cldu and Idu Injection Protocolmentioning
confidence: 99%